Perancangan Implementasi Green Budgeting Pada PT. ABC Menuju Green Company - Hana Tarizkha Coganuli; Desi Adhariani (Politeknik Ganesha Medan, 2023)
Sustainable development is increasingly being developed in this century and to support this green economy approach has been developed. Companies that are aware of this starting to contribute and add environmental management aspects to the strategy roadmap and to accommodate this program budget allocation is required for its implementation. Responding to this, green budgeting methods are now being applied to many institutions. Green budgeting is a budgeting paradigm that prioritizes elements of environmental in the processes of preparation, implementation, monitoring and evaluation. Green budgeting allows organizations to use budgets as a tool to support the achievement of environmental goals. The theory and concepts used is green budgeting based on OECD. This study aims to provide the framework that related to apply the green budgeting concept that is fit with the conditions of the company. This research uses qualitative methods based on case study analysis of manufacturing company. The data used obtained from interviews and documentation that related to the company's budgeting process and green company roadmap. The results show in making the framework design, PT. ABC already has strategic goals related to environmental management which is directed from shareholders and long-term corporate plan. To implement this concept, the company has policy that related such as Blueprint green company document and to report the progress, company has media such as management reports and sustainability reports to inform realization of the program. Then, if this concept is applied, tagging mechanism related with environmental management is needed in preparing the company's annual budget.